2010
DOI: 10.1182/blood.v116.21.2806.2806
|View full text |Cite
|
Sign up to set email alerts
|

Bendamustine + Rituximab as Treatment for Elderly Patients with Relapsed or Refractory Diffuse Large B-Cell Lymphoma.

Abstract: 2806 Background: Current first-line immuno-chemotherapy for diffuse large B-cell lymphoma (DLBCL) is highly effective, curing 50–90% of patients, depending on staging and prognostic factors. Relapsed or refractory patients who are ineligible for transplant or who relapse after transplant generally have a poor prognosis. Aggressive salvage regimens for DLBCL are frequently intolerable and may involve hospitalization for this population of patients. Bendamustin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…[22][23][24] Similarly, bendamustine has limited single-agent activity with an overall response rate of only 38% in relapsed aggressive lymphomas, and yet combinations with rituximab are promising with response rates of 55% even in elderly patients and those with refractory disease. 25,26 Thus, ixabepilone may yet have a role in lymphomas, if the right combination can be developed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24] Similarly, bendamustine has limited single-agent activity with an overall response rate of only 38% in relapsed aggressive lymphomas, and yet combinations with rituximab are promising with response rates of 55% even in elderly patients and those with refractory disease. 25,26 Thus, ixabepilone may yet have a role in lymphomas, if the right combination can be developed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, single‐agent gemcitabine obtains only a 20% overall response rate in aggressive lymphomas, but when combined with other agents, the response rate more than doubles, and gemcitabine‐containing salvage regimens are now commonplace in relapsed aggressive lymphomas 22‐24. Similarly, bendamustine has limited single‐agent activity with an overall response rate of only 38% in relapsed aggressive lymphomas, and yet combinations with rituximab are promising with response rates of 55% even in elderly patients and those with refractory disease 25, 26. Thus, ixabepilone may yet have a role in lymphomas, if the right combination can be developed.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent phase II study of bendamustine as monotherapy showed a 100% ORR and a 73% complete response (CR) in R/R MCL patients [ 39 ]. Preliminary data of another study of bendamustine in combination with rituximab in elderly patients with R/R DLBCL demonstrated an ORR of 52% [ 40 ]. A phase III study of this combination showed better efficacy than a fludarabine-rituximab combination in patients with relapsed follicular, other indolent NHLs and MCL [ 41 ].…”
Section: Cytotoxic Therapiesmentioning
confidence: 99%